ISRAELI-SAUDI PARTNERSHIP: REALITIES AND PROSPECTS - Перепелиця, Григорій; Рогуля, Карина (Навчально-науковий інститут міжнародних відносин КНУ імені Тараса Шевченка, 2023)
In this scientific article, we examine today’s realities and future prospects of the Israeli-Saudi partnership in the context of dynamically evolving Middle Eastern geopolitics. Exploring the multifaceted dimensions of this strategic cooperation, the study delves into the diplomatic relations, security considerations, and economic ties between Israel and Saudi Arabia. Using a comprehensive analytical framework, the study sheds light on the motivations behind this unprecedented regional alliance and examines its implications for the broader Middle East security paradigm. By revealing the intricacies of this diplomatic rapprochement, the article aims to provide valuable information to scholars, politicians and observers interested in the geopolitical dynamics of the Middle East.

У цій науковій статті досліджуються поточні реалії та майбутні перспективи ізраїльсько-саудівського партнерства в контексті близькосхідної геополітики, що динамічно розвивається. Досліджуючи багатогранні виміри цієї стратегічної співпраці, дослідження заглиблюється в дипломатичні відносини, міркування безпеки та економічні зв’язки між Ізраїлем і Саудівською Аравією. Використовуючи комплексну аналітичну базу, дослідження проливає світло на мотиви цього безпрецедентного регіонального альянсу та вивчає його наслідки для ширшої парадигми безпеки Близького Сходу. Розкриваючи тонкощі цього дипломатичного зближення, стаття має на меті надати цінну інформацію науковцям, політикам і спостерігачам, які цікавляться геополітичною динамікою Близького Сходу.
ІЗРАЇЛЬСЬКО-САУДІВСЬКЕ ПАРТНЕРСТВО: РЕАЛІЇ ТА ПЕРСПЕКТИВИ